Unsafe Action on Construction Sites: Identifying Behaviors and Influencing Factors - Hassan, Siti Nor Amalini; Nur Ain Ebas (Recent Trends in Civil Engineering and Built Environment, 2025)
The study aims to identify unsafe actions and factors that influence their behavior. Workers’ irresponsibility is responsible for 80% of accidents. Between January and November 2022, 148 accidents and injuries occurred in the construction industry. Cakna Enterprise Sdn. Bhd. is constructing an additional building for college matriculation minorities in Kelantan, covering 107 acres and 36,698.05 m2. A survey questionnaire was administered to gather data on the workers at Cakna Enterprise Sdn Bhd. The analysis of surveys found that the most unsafe act on the site was to deny orders. With a mean reading of 3.34, time pressure is the working factor that achieves the highest mean reading. Roughly 90% of participants concurred that a significant contributing element to the work factor was time stress. This is due to the need to boost output. When a job is prepared more quickly than it needs to be, employees will choose to take risks to save time and boost output.